2015
DOI: 10.1097/dcr.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs

Abstract: No statistically significant increase in the proportion of patients with anastomotic leak was observed when prescribing nonsteroidal anti-inflammatory drugs for analgesia in the early postoperative period for patients undergoing elective colorectal surgery. Unexpectedly, there was an increased risk of sepsis that warrants further investigation (see video, Supplemental Digital Content 1, http://links.lww.com/DCR/A192, for a synopsis of this study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…In a study by Gorissen et al, patients on NSAIDs had higher anastomotic leakage rates than those not treated with NSAIDs (13.2% versus 7.6%; p = 0.010) [ 54 ]. However, a multicenter retrospective study found no statistically significant increase in the proportion of patients with anastomotic leak when prescribing nonsteroidal anti-inflammatory drugs for analgesia in the early postoperative period for patients undergoing elective colorectal surgery [ 55 ]. This finding is supported by other studies, showing that use of NSAIDs did not increase the risk of anastomotic leakage after anterior resection for rectal cancer [ 56 , 57 ].…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…In a study by Gorissen et al, patients on NSAIDs had higher anastomotic leakage rates than those not treated with NSAIDs (13.2% versus 7.6%; p = 0.010) [ 54 ]. However, a multicenter retrospective study found no statistically significant increase in the proportion of patients with anastomotic leak when prescribing nonsteroidal anti-inflammatory drugs for analgesia in the early postoperative period for patients undergoing elective colorectal surgery [ 55 ]. This finding is supported by other studies, showing that use of NSAIDs did not increase the risk of anastomotic leakage after anterior resection for rectal cancer [ 56 , 57 ].…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…The physicians are also encouraged to use the lowest effective dose for the shortest duration of a selective COX-2 inhibitor. In surgical point of view, the use of any NSAIDs including selective COX-2 inhibitors in the setting of gastrointestinal anastomosis has been concerned because some studies have suggested that NSAIDs may impair anastomotic healing [38][39][40] . Recently, a meta-analysis of clinical and experimental studies in 2014 has indicated a strong link between anastomotic leakage and the use of non-selective NSAIDs, but not the use of selective COX-2 inhibitors [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Findings related to the risks of anastomotic leak in bowel surgery in relation to the use of NSAIDs are conflicting (Hakkarainen et al 2015, Paulasir et al 2015). Although some studies reported an increased frequency of anastomotic leak in patients treated with nonselective NSAIDs and decreased anastomotic leak with the use of selective COX-2 inhibitors, the effects of NSAIDs remain unclear.…”
Section: Multimodal Analgesiamentioning
confidence: 99%